The Relationship Between Family Support and Achievement Motivation of Residents Learning Package C at PKBM Farilla Ilmi - M Alsidiq; Ismaniar Ismaniar (Universitas Negeri Padang, 2023)
This research was motivated by the low learning outcomes of the residents studying Package C at PKBM Farilla Ilmi Padang. This is presumably due to the lack of running of the family's role in supporting the successful achievement of learning citizens. The purpose of this study is to see whether there is a relevant relationship between family support and achievement motivation of residents studying Package C at PKBM Farilla Ilmi Padang. This type of research is quantitative correlational. The population in this study were all residents studying Package C at PKBM Farilla Ilmi Padang in 2022, totaling 63 people, with a sample size of 32 people and to collect data using questionnaires or questionnaires that have completed validity and reliability testing. The data analysis technique used bivariate correlation analysis technique. The statistical formula used is the percentage formula and the Spearman rank/range order correlation formula. Research results 1). Family support is categorized as less supportive; 2). Achievement motivation of learning residents is categorized as lacking; 3). There is a significant relationship between the relationship between family support and achievement motivation of learning residents. The results of the statistical test of the spearman rho formula obtained rcount = 0.875, the value of 0.875 is declared strong.